Diminishing covariation bias in women with a negative body evaluation and the potential roles of outcome aversiveness and interpretation of social feedback. (March 2018) - Alleva, Jessica M.; Stuijfzand, Bobby G.; Martijn, Carolien
Highlights: We investigated covariation bias for the relation between women's own body and negative social feedback. Women with a more negative body evaluation demonstrated covariation bias. Manipulating stimulus-outcome contingencies diminished covariation bias. Manipulation of the covariation bias coincided with improved state body evaluation. Outcome aversiveness coincides with bias but is not specific to women's own body. Abstract: Women with a more negative body evaluation perceive that their body is associated with more negative social feedback. This covariation bias could reinforce negative body evaluation. We investigated whether covariation bias could be diminished and explored the potential roles of outcome aversiveness and interpretation of negative social feedback associated with one's body. Ninety-seven undergraduate women completed a computer task wherein photos of their body, a control woman's body, and a neutral object were followed by negative social feedback or nothing. When the relation between each category and the negative feedback was random, women with a more negative body evaluation perceived more negative feedback following their body. They also experienced negative feedback following their body and the control woman's body as more aversive. After a manipulation block, women with a more negative body evaluation no longer perceived more negative feedback for their body. These effects coincided with improvements in state body evaluation.